Content-based Image Retrieval using Texture and Color Features - AL-Asadi, Abbas Hanon (University of Thi-Qar Journal of Science, 2013)
The emergence of multimedia technology and the rapidly expanding image collections on theInternet have attracted significant research efforts in providing tools for effective retrieval andmanagement of visual data. Content-based image retrieval has been an active area of research over last decade. In this paper, a content-based image retrieval system is presented. It supports querying by example to retrieve images from the images database according to their texture and color features. For feature extractions, Gray-Level Co-occurrence Matrix (GLCM) and color histogram of HSV have been used. The results appeared quite satisfactory.